2003
DOI: 10.1002/j.1939-4640.2003.tb02668.x
|View full text |Cite
|
Sign up to set email alerts
|

Cavernous Neurotomy Causes Hypoxia and Fibrosis in Rat Corpus Cavernosum

Abstract: The etiologies of erectile dysfunction (ED) after nerve-sparing radical prostatectomy have not been clearly elucidated. The aim of this study was to evaluate the effects of cavernous nerve injury on cavernous fibrosis, and to consider measures to prevent irreversible damage to the cavernous tissues. Twenty male Sprague-Dawley rats constituted the study population. The animals were divided into 2 groups; group 1 consisted of sham-operated rats (n = 10), and group 2 consisted of rats that underwent incision of b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
208
1
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 257 publications
(229 citation statements)
references
References 19 publications
14
208
1
4
Order By: Relevance
“…Similarly to other studies, they concluded that progressive fibrosis in the corpora cavernosa after radical prostatectomy resulted from denervation and/or an ischemic process (19). Several human and animal studies support the hypothesis of maintaining adequate penile oxygenation by preserving neurovascular bundles and thus erectile function, may play an important role in preventing irreversible penile fibrotic changes (8,14,15). User et al performed a study on postpubertal rats and grouped them according to bilateral or unilateral cavernous nerve transection versus a sham operation (14).…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Similarly to other studies, they concluded that progressive fibrosis in the corpora cavernosa after radical prostatectomy resulted from denervation and/or an ischemic process (19). Several human and animal studies support the hypothesis of maintaining adequate penile oxygenation by preserving neurovascular bundles and thus erectile function, may play an important role in preventing irreversible penile fibrotic changes (8,14,15). User et al performed a study on postpubertal rats and grouped them according to bilateral or unilateral cavernous nerve transection versus a sham operation (14).…”
Section: Discussionmentioning
confidence: 71%
“…Potential pathophysiology of ED that may occur after RP has been widely discussed in several studies (13)(14)(15) and there are studies evaluating the penile length changes after RP (7,12,16). The mechanism responsible for the reduction in penile length after RP has not been elucidated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent experimental model, penile tissue from rats undergone bilateral incision of cavernosal nerves 3 months earlier showed a significant overexpression of hypoxia-related substances like TGF-beta and collagen I and III compared with the same tissue from a control group. 18 Using a similar neurogenic ED model, User et al 19 documented a significant apoptosis in the subalbugineal smooth muscle cells following bilateral neurotomy of the rat penis. Histomorphometric studies have shown that when a high proportion of trabecular smooth muscles is replaced by collagen, the cavernoocclusive mechanism is lost with subsequent venogenic ED.…”
Section: Patients Bother For Sexual Function After Nsrpmentioning
confidence: 99%
“…Sustained hypoxia causes overexpression of transforming growth factor-b 1. 26 This leads to increased synthesis of endothelin-1, which is a constrictor of penile smooth muscle and a profibrotic agent. 27 This fibrosis leads to decreased EF.…”
Section: Pathophysiologymentioning
confidence: 99%